Efektivitas Penerapan Media Gambar Bangun Datar dalam Meningkatkan Keberhasilan Belajar Matematika pada Siswa Autis Kelas VII SLB Negeri Autis Kupang - Manafe, Agnestia Kotten; Wangge, Vinsensius; Selan, Ot Bill Wilson; Sene, Chamelya Vivi Crystanty; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of using visual media in improving mathematics learning outcomes among seventh-grade autistic students at the Kupang State Special School for Autistic Children. The study employed the Classroom Action Research (CAR) method, conducted in two cycles, with a pre-test and post-test design in each cycle. The research subjects consisted of three mildly autistic seventh-grade students. Data collection techniques were carried out through learning outcome tests, observation of learning activities, and documentation, while data analysis was conducted by comparing the pre-test and post-test results in each cycle to see the increase in student learning success. The results showed that the use of visual media was able to gradually improve the mathematics learning success of autistic students. This was indicated by a significant increase in learning outcomes from the pre-test to the post-test in cycle I and a further increase in cycle II. Thus, it can be concluded that the use of visual media is effective in improving the mathematics learning success of seventh-grade autistic students at the Kupang State Special School for Autistic Children.